O crédito consignado no quadro da aposentadoria rural no campo sergipano - Santana, Gleise Campos Pinto (2016)
The present study analyzes the insertion of financial capital in the countryside as from the payroll loans intended to the rural retirees. The purpose is to evaluate the functionality of the rural retirement in the current context of capitalist relations, considering that the retiree has direct access to the credit system that increasingly imprisons his income, making him a hostage of the financial system. This study recognizes the dynamics of the production space and emphasizes the importance of denudate the various ways of production. Therefore, it is considered that rural areas has been incorporated into the socio-metabolic system of the capital, each time more dynamically, exposing the combined relations which favor their expanded reproduction. The countryside will appear as a place to be modified. All kinds of "alternative" investments to the peasant production are suggested. It is noteworthy that, in combination to the logic of rural development at the present time, a masking purpose of the centrality that the soil continues to exercise for the social reproduction of the populations living in this portion of space is presented as central to the State and the capital. In view of this, it becomes necessary to analyze the rural areas as part of the totality, in order to expose its dependence on the on State and the market. This state, allied with the capitalism, has put the elderly retired of the countryside increasingly trapped in chains of financialization, since along with the achievement of the rural pension provided by the Social Security, comes the fetish of the easy money provided by the credit system. At the limits of this dependence, the rural retirement gains social relevance and economic importance in the Brazilian countryside.